The role of financial efficiency in renewable energy demand: Evidence from OECD countries - Koksal, Cihat; Katircioglu, Setareh; Katircioglu, Salih (Academic Press Ltd- Elsevier Science Ltd, 2021)
This study searches the role of the financial system efficiency in renewable energy demand for the case of the 36 OECD countries. Numerous financial system proxies are used between 1990 and 2017. Results show that financial system proxies generally are poorly linked to the renewable energy demand of the OECD member states. Although the coefficient of the overall financial development proxy is positively significant for renewable energy demand, the coefficients of financial efficiency are insignificant. The present study finds significant effects of the overall financial markets and institutions on renewable energy demand; however, any vital link between financial system efficiency and renewable energy demand could not be obtained in the OECD countries. Policy implications regarding this major finding are provided in the current study.
Keywords: Financial efficiency; Renewable energy; Innovation; Paris agreement; OECD